New record of Lithodidae (Crustacea Decapada, Anomura) from the Antarctic (Bellingshausen Sea). - García-Raso, José Enrique; Manjón-Cabeza, María Eugenia; Ramos, Ana; Olaso-Toca, Luis Ignacio (Polar Biology, 2005)
During the Bentart-2003 Cruise, carried out during austral summer 2003 in the Bellingshausen Sea, three species of Lithodidae, Paralomis birsteini, Lithodes murrayi and Neolithodes capensis, were caught from 218 m to 1947 m. With these captures the presence of L. murrayi in Peter I Island is confirmed, the distribution area of N. capensis is greatly increased and the captures of N. capensis and P. birsteini represent the first lithodid record known from the Antarctic continental slope. Also, these records show large and discontinuous distributions, which illustrate that many distribution patterns of Antarctic species are more an artefact of limited studies than representing actual distribution Sí